2017
DOI: 10.18203/2349-3933.ijam20171996
|View full text |Cite
|
Sign up to set email alerts
|

CSF flowmetry: an innovative technique in diagnosing normal pressure hydrocephalus

Abstract: Background: Normal pressure hydrocephalus is a very gloomy entity. The objective of this study is to analyse aqueductal velocity parameters by phase contrast MRI CSF flowmetry in Idiopathic Normal pressure hydrocephalus patients (NPH).Methods: This study consists of 72 participants which included 36 patients and 36 matched healthy controls. The study stretched over three years in multicentre tertiary research hospitals using 3T MRI scanner. Both normal MRI sequences and phase contrast CSF flowmetry was done fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…After sequence acquisition, images are retrieved in sets of three different contrasts for each plane: re-phased image (magnitude of flow compensated signal), phase image (phase of difference signal), and magnitude (magnitude of difference signal). Since it reflects the phase shift, the phase image is more sensitive to CSF flow detection than the magnitude image [3, 4, 9]. The acquisitions are synchronized with the cardiac cycle generating images with velocity information providing the ability to calculate stroke volume, mean velocity, and peak flow in systole and diastole.…”
Section: Mri Protocolmentioning
confidence: 99%
“…After sequence acquisition, images are retrieved in sets of three different contrasts for each plane: re-phased image (magnitude of flow compensated signal), phase image (phase of difference signal), and magnitude (magnitude of difference signal). Since it reflects the phase shift, the phase image is more sensitive to CSF flow detection than the magnitude image [3, 4, 9]. The acquisitions are synchronized with the cardiac cycle generating images with velocity information providing the ability to calculate stroke volume, mean velocity, and peak flow in systole and diastole.…”
Section: Mri Protocolmentioning
confidence: 99%
“…Senger KPS et al, 2020 [12] also reported that stroke volume of >42 microL/cycle is shown to predict good response after CSF shunting.…”
Section: Discussionmentioning
confidence: 97%
“…Phase contrast MRI CSF flowmetry can be used for qualitative and quantitative assessment of CSF flow abnormality in all the previously mentioned neurological condition [18]. Many parameters have been used for assessment of CSF flow by PC MRI including flow, and velocity parameter, stroke volume, peak systolic velocity, mean systolic velocity, forward flow volume, and backward flow volume [10].…”
Section: Discussionmentioning
confidence: 99%
“…Normal pressure hydrocephalus is one of the few treatable causes of dementia, but it is difficult to accurately differentiate it from BA. PC MRI provides a non-invasive tool for diagnosis of NPH and differentiates it from brain atrophy [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation